Lessons in decoration from the Qurʾanic Sūrah al-Zukhruf (Gold Adornments) - Spahic, Omer (IIUM Press, International Islamic University Malaysia, 2021)
This paper discusses three lessons in decoration from the Qurʾanic chapter, or sūrah, al-Zukhruf (gold adornments). The lessons recognise and deal with decoration as an intrinsic human pursuit, a means of deception, and a means for enhancing and promoting the truth. Each lesson is discussed in separate sections, which are titled in the manner of the essence of the lessons. The paper concludes that the realm of decoration is inborn and instinctive. Its potential impact on human emotions and psyche is such that it can influence man’s behavioural pattern. As a weak and wavering creation, it will be burdensome if too much of worldly beauty, splendour and prosperity is placed at his disposal. Thus blinded, most persons would lose sight of all moral and spiritual considerations and become egocentric, insatiable, and cruel. The meaning of inherent beauty, splendour and wealth will then be lost forever in the process. The three lessons are entwined with the nucleus and main emphasis of the sūrah, that is, the exposition of the contrasts between the beauty and glory of the truth and revelation and the false glitter of other counterfeit alternatives. The contents of the lessons represent the gist of the Islamic tawḥīdic (God’s Oneness) worldview.